Study of parking parameters and parking management in Hospital Tengku Ampuan Afzan (HTAA) - Liew, Tzun Ming (2016)
Parking is regarded as an integral part of urban transportation system, and the increase in the number of vehicles had caused problems with parking in major cities around Malaysia. The Hospital Tengku Ampuan Afzan (HTAA) in Kuantan is not sparred from this problem too, while the number of patients and staffs at the hospital keeps increasing each year, the number of parking lots in the car park are still the same, which had caused difficulties for its visitors to search for parking, and contributed to the illegal parking by the roadside along the main entrances. This study aims at assessing the supply and demand of the car parking system as well as the parking parameters in Hospital Tengku Ampuan Afzan (HTAA), Kuantan. Besides, this study will also present the actual figures of the number of illegally parked vehicles within the hospital compound, as well as those by the roadside along the main entrances. This data, along with the other parking parameters studied in this study, will present the actual parking demand in HTAA. Corrective measure is suggested in this study to improve the parking woes in HTAA. In this study, parking supply is defined as the number of parking lots provided at the hospital, and parking demand is meant by the summation of parking accumulation and the number of illegally-parked vehicles. License plate survey is chosen for this study, as it provides data of higher accuracy and consistency. The methodology of this study involved data collection, data analysis and recommendations to improve the situation.